2014
DOI: 10.1177/1010539514552702
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Disease-Associated Malnutrition in China

Abstract: Disease-associated malnutrition (DAM) is a well-recognized problem in many countries, but the extent of its burden on the Chinese population is unclear. This article reports the results of a burden-of-illness study on DAM in 15 diseases in China. Using data from the World Health Organization (WHO), the China Health and Nutrition Survey, and the published literature, mortality and disability-adjusted life years (DALYs) lost because of DAM were calculated; a financial value of this burden was calculated followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The following diseases/conditions associated with malnutrition were identified from a search of articles estimating the burden of disease from malnutrition: breast cancer, COPD, CRC, CHD, dementia, depression, musculoskeletal disorders, stroke, chronic pancreatitis, and head and neck cancers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following diseases/conditions associated with malnutrition were identified from a search of articles estimating the burden of disease from malnutrition: breast cancer, COPD, CRC, CHD, dementia, depression, musculoskeletal disorders, stroke, chronic pancreatitis, and head and neck cancers.…”
Section: Methodsmentioning
confidence: 99%
“…Malnutrition has been defined as the presence of any 1 of the following 3 risk factors relating to underweight, ie, protein–energy deficiency and anemia as respectively measured by body mass index (BMI) ≤18.5, serum albumin <35 gm/L, and hemoglobin <120 gm/L in men or <110 gm/L in women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It includes an inability to ingest or absorb nutrients, as well as the increased energy needs related to the disease or restricted diet as a result of the treatment. 6 Table 1 shows that malnutrition accounted for 15% (42/274) of the health conditions described in the studies reviewed. The study classification by condition mirrors the health circumstances frequently associated with nutritional problems.…”
Section: Malnutrition Conditionmentioning
confidence: 99%
“…5 Other definitions of malnutrition include the presence of any of the three risk factors: underweight (ie, BMI <18.5 kg/m 2 in adults or <5 th percentile of a standardized distribution among children), anemia (ie, hemoglobin <110 g/L for females or 120 g/L for males), or protein-energy malnutrition (ie, serum albumin <35 g/L). 6 Many studies have shown that the prevalence of malnutrition in North American, European, Asian, Australian, and Latin American hospitals can range from 20% to ≥50%. 4,7 However, malnutrition is not limited to patients in hospitals; a UK study found that 93% of the estimated 3 million people malnourished or at risk of malnutrition live in the community.…”
mentioning
confidence: 99%